Design for Monitoring Blood Pressure, Non-Invasive Blood Sugar, Weight, and Body Temperature Based on Internet of Things - Muhammad Nur Fariz; Jamaaluddin (Procedia of Engineering and Life Science, 2021)
In adults to the old age, check health conditions such as blood pressure, blood s ugar levels, and others are needed regularly. Medical devices generally only be operated by doctors. Healthcare companies always develop medical devices for efficiency in use and minimize costs in manufacture. In this study, researchers made a design for monitoring blood pressure, non-invasive blood sugar, weight, and body temperature based on the Internet of Things. This tool uses NodeMCU microcontroller, which processes sensor MAX30100 and DS18B20. The MAX30100 sensor is used to detect blood pressure and blood sugar non-invasive. By put finger index on the sensor, the results will display after 20 seconds. DS18B20 sensor is used to measure realtime body temperature by clamp the sensor to the armpit. Load Cell sensors and the HX711 module are used to measure body weight.Results on measurements on LCD 20x4 and android using the Blynk application with the internet.Test analysis with a compare of the manufacturer's standard tools. The results, accuracy of tool are 94.78% and 93,37% in the measurement systole and diastole, 93,21% in measuring blood sugar, 96,55% in measuring body temperature, and 98,27% in measuring body weight. The results on Android can display if there is an internet or wifi connection without place restrictions.